The use of negative bias potential for structural engineering of vacuum-arc nitride coatings based on high-entropy alloys - Sobol, O. V.; Andreev, A. A.; Gorban, V. F.; Postelnyk, H. O.; Stolbovoy, V. A.; Zvyagolsky, A. V.; Dolomanov, A. V.; Kraievska, Zh. V. (My University, 2019)
The effect of negative bias potential (Ub = -40, -110, and -200 V) during the deposition of multi-element coatings on their composition, structure and mechanical properties was studied. It was established that during the transition from a multi-element alloy to a nitride, a single-phase state possible to form on its basis (based on the fcc metal lattice, structural type NaCl). In this case, the composition (FeCoNiCuAlCrV)N of coatings with increasing Ub is depleted by the element with the lowest enthalpy of formation of nitride (Cu). In (AlCrTiNbSi)N and (AlCrTiZrNbV)N coatings, the content of low-mass elements (Si and Al) decreases with increasing Ub. In (TiZrHfVNb)N coatings of strong nitride-forming elements with increasing Ub to 200 V, the composition practically does not change. The structure of such coatings is characterized by the presence of a texture with the [111] axis. The presence of weak nitride-forming elements in (FeCoNiCuAlCrV)N coatings leads to the formation of texture [110] for large Ub = 110…200 V. In such coatings, the hardness does not exceed 35 GPa. It is shown that to achieve high hardness at high Ub it is necessary to increase the content in the high-entropy alloy of elements with high nitride-forming ability. In this case, in (TiZrHfVNb)N coatings (made of strong nitride-forming elements with a large mass) at Ub = 200 V, the hardness exceeds 45 GPa.

Досліджено вплив негативного потенціалу зміщення (Ub = -40, -110 і -200 В) при осадженні багатоелементних покриттів на їх склад, структуру і механічні властивості. Встановлено, що при переході від багатоелементного сплаву до нітриду на його основі можливе формування однофазного стану (на основі ГЦК металевої решітки структурний тип NaCl). При цьому склад (FeCoNiCuAlCrV)N-покриттів зі збільшенням Ub збіднюється елементом з найменшою ентальпією утворення нітриду (Cu). У (AlCrTiNbSi)N- і (AlCrTiZrNbV)N-покриттях зі збільшенням Ub зменшується вміст елементів з малою масою (Si і Al). У (TiZrHfVNb)N-покриттях, що складаються з сильних нітрідоутворюючих елементів з великою масою, при збільшенні Ub до 200 В склад практично не змінюється. Структура таких покриттів характеризується наявністю текстури з віссю [111]. Наявність слабких нітрідоутворюючих елементів у (FeCoNiCuAlCrV)N-покриттях призводить при великих Ub = 110…200 В до формування текстури [110]. У таких покриттях твердість не перевищує 35 ГПа. Показано, що для досягнення високої твердості при великих Ub необхідно збільшувати вміст у високоентропійному сплаві елементів з високою нітрідоутворюючою здатністю. При цьому в (TiZrHfVNb)N-покриттях (з сильних нітрідоутворюючих елементів з великою масою) при Ub = 200 В твердість перевищує 45 ГПа.
Використання негативного потенціалу зміщення для структурної інженерії вакуумно-дугових нітридних покриттів на основі високоентропійних сплавів
Keywords: hardness; chemical reactions; structural engineering; nitride coatings; mechanical characteristics; осадження; хімічні реакції; механічні властивості; твердість